1994
DOI: 10.1063/1.870627
|View full text |Cite
|
Sign up to set email alerts
|

Edge plasma fluctuations and transport in a reversed-field pinch

Abstract: Edge plasma fluctuations are studied with inserted triple Langmuir probes and magnetic coils in the TPE-1RM20 reversed-field pinch [Yo Yagi et al.]. l\vo-point measurements show that density and potential fluctuations have relatively low mode numbers (m <3, n <40). High coherence (y=0.5) with magnetic field fluctuations and similar mode spectra suggest that density and potential fluctuations are mainly caused by electromagnetic turbulence. Broadband magnetic fluctuations are dominated by m =0, low-n modes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
36
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 15 publications
10
36
0
Order By: Relevance
“…In tokamaks, nonambipolar ion losses near the plasma periphery are also proposed as a possible mechanism for the establishment of transport barriers at the edge with scale lengths comparable to the poloidal gyroradius [1]. In RFPs, the structure of the plasma potential at the edge, measured in different devices, reveals that the radial electric field is directed outward in the SOL [3,9] and inward right inside the plasma surface [5,[9][10][11].This behavior was already pointed out to exhibit a surprising analogy to that found in tokamaks and stellarators [11], despite the different physics expected in a RFP configuration. In fact, the large magnetic fluctuation level ͑b͞B ϳ 1%͒ and the wide spectrum of unstable MHD modes characteristic of this configuration result in a wide stochastic region where the higher electron diffusivity should give rise to an outward directed radial ambipolar electric field to restrain the electrons.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In tokamaks, nonambipolar ion losses near the plasma periphery are also proposed as a possible mechanism for the establishment of transport barriers at the edge with scale lengths comparable to the poloidal gyroradius [1]. In RFPs, the structure of the plasma potential at the edge, measured in different devices, reveals that the radial electric field is directed outward in the SOL [3,9] and inward right inside the plasma surface [5,[9][10][11].This behavior was already pointed out to exhibit a surprising analogy to that found in tokamaks and stellarators [11], despite the different physics expected in a RFP configuration. In fact, the large magnetic fluctuation level ͑b͞B ϳ 1%͒ and the wide spectrum of unstable MHD modes characteristic of this configuration result in a wide stochastic region where the higher electron diffusivity should give rise to an outward directed radial ambipolar electric field to restrain the electrons.…”
mentioning
confidence: 99%
“…Hc, 52.35.Ra, 52.40.Hf, 52.70.Ds In recent years, the structure of the radial electric field at the edge of tokamaks and stellarators has been investigated to establish the stabilizing effect on the transport driven by electrostatic fluctuations [1]. Since in most reversed field pinch (RFP) experiments [2] the particle transport is driven mainly by electrostatic fluctuations [3][4][5][6], there is nowadays a growing interest on the structure of the plasma potential and of the radial electric field at the edge to study the possibility of achieving enhanced confinement regimes also in RFPs.A common feature of tokamak and stellarator experiments is a radial electric field pointing inward right inside the last closed flux surface (LCFS) and outward in the scrape off layer (SOL) generated by limiters (see, for example, [7]). In tokamaks, this radial behavior has been interpreted with different mechanisms, including ion losses due to finite Larmor radius (FLR) effects [7,8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we analyze a pulsed poloidal current drive (PPCD) plasma. In this case, the normalized cutoff radius is about 0.8-0.9 m. This region is close to the reverse field surface, and the fluctuation changes rapidly [14,15].…”
Section: Experiments In Tpe-rxmentioning
confidence: 99%
“…For example, the improved high theta mode on the TPE-1RM20 device demonstrates high beta and improved energy confinement in the H $ 2 region. 3 The magnetic and=or electrostatic fluctuations on the dynamo event have been investigated in several RFP devices, [4][5][6][7][8][9][10][11] where it has been shown that the RFP transport in the plasma core region mainly depends on the magnetic fluctuation, whereas the electrostatic fluctuation plays a significant role in the edge region. The energy of the core region is carried by a fast electron to the edge region.…”
mentioning
confidence: 99%